Narrative Review of Sustainable Vegetable Production Using Efficiency and Environmental Sustainability Approaches - Hansley Richie; Haneen Basori; Niken Rahmawati; Betania Barimbing; Nurhayati (Journal of Business Economics and Agribusiness, 2026)
This study aims to analyze the implementation of Sustainability Principle 2 in vegetable production systems by synthesizing recent scientific literature. The review focus on resource-efficient and beneficial agricultural practices that support sustainable vegetable cultivation. A literature narrative review method was used to analyze studies published between 2016 and 2026 on vegetable production practices aligned with Sustainability Principle 2. The analysis synthesizes findings across key themes, including soil health and fertility, water and nitrogen use efficiency, chemical inputs, energy use, and sustainable cultivation practices such as crop rotation, agroforestry, and the adoption of green technologies. The findings imply that traditional vegetable production methods frequently rely heavily on the use of energy, water, fertilizer, and pesticides. Environmental problems like greenhouse gas emissions, nutrient losses, soil degradation, and water pollution can result from this reliance. Nonetheless, a number of different strategies show encouraging promises for enhancing sustainability. For instance, it has been demonstrated that organic farming practices enhance soil quality and boost soil carbon sequestration. Furthermore, hydroponic systems enable more accurate control over the use of nutrients and water. Additionally, decrease reliance on synthetic agrochemicals while preserving production efficiency can be achieved by applying ecological technologies and improving input management techniques.